A new species of the pontoniine shrimp genus Onycocaris Nobili, 1904 (Crustacea: Decapoda: Caridea: Palaemonidae) from Sagami Bay, central Japan - Komai, Tomoyuki; Itou, Isamu (Zootaxa, 2012)
The pontoniine shrimp genus Onycocaris Nobili, 1904 currently contains 18 species, all known from the Indo-WestPacific. In this study, a new species of the genus, O. hayamaensis, is described and illustrated on the basis of fourovigerous female and three male specimens collected from Sagami Bay, central Japan, at shallow subtidal depths of5–6 m. The specimens lived in internal cavities of an unidentified species of a haliclonid sponge, Haliclona sp. Thisnew species is referred to the O. quadratophthalma (Balss, 1921) species group, represented by four species, i.e., O.balssi Bruce, 2011, O. fujinoi Bruce, 2011, O. quadratophthalma, and O. trullata Bruce, 1978. Differentiatingcharacters between the new species and the latter four species are discussed. The present new species exhibits strongsexual dimorphism in the second pereopods and heterochaely in the male second pereopods, though these traits are notfully documented in some of other congeneric species. Diagnostic characters derived from the second pereopods should be treated carefully.